2004
DOI: 10.1073/pnas.0406344101
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory, recognition memory, and the hippocampus

Abstract: There is wide agreement that spatial memory is dependent on the integrity of the hippocampus, but the importance of the hippocampus for nonspatial tasks, including tasks of object recognition memory is not as clear. We examined the relationship between hippocampal lesion size and both spatial memory and object recognition memory in rats. Spatial memory was impaired after bilateral dorsal hippocampal lesions that encompassed 30 -50% total volume, and as lesion size increased from 50% to Ϸ100% of total hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
577
3
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 825 publications
(635 citation statements)
references
References 39 publications
37
577
3
8
Order By: Relevance
“…It has been suggested that spatial memory requires a more complete hippocampal function than does recognition memory (Broadbent et al, 2004) so it seems that the 4-week treatment was enough to improve the function in different brain areas related to recognition memory but not in the hippocampus. A longer-lasting rosiglitazone treatment also rescued impaired spatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that spatial memory requires a more complete hippocampal function than does recognition memory (Broadbent et al, 2004) so it seems that the 4-week treatment was enough to improve the function in different brain areas related to recognition memory but not in the hippocampus. A longer-lasting rosiglitazone treatment also rescued impaired spatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that examine recognition by monitoring spontaneous exploration of familiar and novel stimuli, monkeys with selective hippocampal or parahippocampal cortex damage that show little or no deficit in DNMS have severe and rapidly apparent deficits on the spontaneous novelty exploration task Nemanic et al, 2004). In rats, some studies report no deficit (e.g., Mumby, 2001;Mumby et al, 2002;Winters et al, 2004), whereas other studies have observed impairment at long delays Hammond et al, 2004), or following a large amount of damage to the hippocampus (Broadbent et al, 2004). In contrast to the modest and variable deficit observed following damage to the hippocampus, ablation of the perirhinal cortex consistently results in a severe and rapidly developing deficit in both kinds of recognition memory tasks in monkeys (Nemanic et al, 2004) and in rats (Mumby et al, 2002;Winters et al, 2004;Norman and Eacott, 2005;Winters and Bussey, 2005).…”
Section: Hippocampusmentioning
confidence: 98%
“…Hippocampal damage from ibotenic acid disrupted recognition memory in the novel object recognition task and the visual paired comparison task (Clark et al, 2000;Broadbent et al, 2004). Furthermore, an intrahippocampal WIN 55,212-2, also impaired performance of the novel object recognition task (Kosiorek et al, 2003;Suenaga and Ichitani, 2008).…”
Section: Discussionmentioning
confidence: 99%